Arabidopsis thaliana β-glucosidase BGLU15 attacks flavonol 3-O-β-glucoside-7-O-α-rhamnosides. (January 2015) - Roepke, Jonathon; Bozzo, Gale G.
Graphical abstract: Rapid disappearance of kaempferol 3- O -β-glucoside-7- O -α-rhamnoside (1 ) and quercetin 3- O -β-glucoside-7- O -α-rhamnoside (2 ) occurs in Arabidopsis thaliana during abiotic stress recovery. Here, it is shown that a β-glucosidase, BGLU15, is specific for the 3- O -β-glucoside position of compounds1 and2, yielding kaempferol 7- O -α-rhamnoside (3 ) and quercetin 7- O -α-rhamnoside (4 ), respectively. Highlights: Flavonol 3- O -β-glucoside-7- O -α-rhamnoside hydrolysis occurs in Arabidopsis during abiotic stress recovery. Phylogenetic and gene expression analyses imply a β-glucosidase, BGLU15, is involved in this catabolism. BGLU15 is specific for β-linked glucosides of flavonol 3- O -β-glucoside-7- O -α-rhamnosides. Abstract: Kaempferol and quercetin 3- O -β-glucoside-7- O -α-rhamnoside (K3G7R and Q3G7R, respectively) are major flavonol bisglycosides accumulating in Arabidopsis thaliana with synergistic abiotic stresses (i.e., nitrogen deficiency and low temperature, NDLT). However, these molecules disappear rapidly during recovery from NDLT. Typically, catabolism of related chemicals relies on β-glucosidase (BGLU) action. Evidence for flavonol 3- O -β-glucoside-7- O -α-rhamnoside BGLU activity is provided here. Major losses of Q3G7R and K3G7R coincided with an approximate 250% induction in flavonol 3- O -β-glucoside-7- O -α-rhamnoside BGLU activity within 2 days of NDLT recovery relative to plants cultured under nitrogen sufficiency and high temperature (NSHT, control). QTOF-MS/MS established the product of Q3G7R hydrolysis in the presence of Arabidopsis cell free extracts was quercetin 7- O -α-rhamnoside. A phylogenetic analysis of the Arabidopsis glycoside hydrolase family 1 identified BGLU15 (At2g44450) and five other members that cluster with Fabaceae hydrolases known to attack isoflavones and isoflavonoids, which are structurally somewhat related to flavonol 3- O -β-glucoside-7- O -α-rhamnosides. Real time quantitative PCR analysis established a 300% higher expression of BGLU15 within 1 day of the recovery from NDLT relative to control plants; lower or negligible changes in expression were evident for the remaining BGLUs. Recombinant thioredoxin-His6 -tagged mature BGLU15 protein was expressed in Escherichia coli and purified to homogeneity. A comparison of a wide spectrum of β-glucosides showed that recombinant BGLU15 preferentially hydrolyses the 3- O -β-glucosides of flavonols, but does not attack quercetin 3- O -α-rhamnoside, quercetin 3- O -β-galactoside and rutin. BGLU15 displayed the highest catalytic efficiency for Q3G7R and K3G7R yielding their respective 7- O -rhamnosides as products; flavonol 3- O -glucosides were also attacked, albeit with lower efficiency. Together, it appears the loss of flavonol 3- O -β-glucoside-7- O -α-rhamnosides in Arabidopsis is dependent upon the enzyme-mediated cleavage of the 3- O- β linked glucose moiety.